The Effect of the Use of Picture/Image as a Supporting Tool of Instructional Management of Scientific Approach on the Writing Skill Improvement - Desi Wulansari (Universitas Syiah Kuala, 2020)
One of the efforts to solve the students’ problems in writing is to use picture media, combined with scientific approach. This research aims at finding aspects of writing that can be improved through the combination of such media and approach. In addition, the research also intends to see which aspects of writing can be the most significantly improved by means of such a combination approach. Other objective is to find if students’ response toward the use of picture of scientific approach is positive. This is a quantitative approach with experimental study of randomized pretest-posttest group design. The samples are selected by using random sampling technique. The instruments are tests and questionnaires. The data is analyzed by using t-test for test and percentage for questionnaire. The result showed that picture media combined with scientific approach can improve students’ writing skill in those five areas of writing skill (content, vocabulary, organization, language use and mechanic). Out the five areas, the ‘language use’ is the most significantly improved. Other finding showed that most students’ responses toward the use of picture media and scientific approach are positive. Thus, it can be recommended that teachers may use such a combination instructional approach in teaching writing. In conclusion, the use of picture media combined with scientific approach may be an appropriate choice for the teachers in their efforts to improve their students’ writing skill.